Individual Relationship Conflict, Work Engagement dan Technical Performance :Studi Kuantitatif Pada Jabatan Fungsional Auditor - Tarman Budianto (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
The auditor has complex duties and responsibilities and involves the interests of various stakeholders who are vulnerable to various conflicts. This study aims to investigate: (1) The effect of work engagement on the technical performance of auditors, and (2) the moderating role of individual relationship conflict on the effect of work engagement on the technical performance of auditors. This research was conducted using a quantitative method with a survey approach to examine the effect of the variables formulated in the hypothesis. Hypothesis testing is done by linear regression analysis and PROCESS analysis technique. This study involved 116 auditors from various regions in Indonesia as respondents. The results show that work engagement has a significant positive effect on technical performance. In addition, individual relationship conflict significantly moderates (weakens) the positive effect of work engagement on technical performance. The results of this study validate the work engagement theory (Bakker et al. 2009). Future research is suggested to explore other conflicts (eg task conflict) because they are predicted to weaken performance. Practically, this finding can be a reference for practitioners/managers and organizational leaders that to improve auditor's technical performance, it can be done by increasing auditor engagement and minimizing the potential for individual relationship conflicts to arise.